Non-traditional security threats and management of border security in Malaysia : 2001-2016 - Muhammad Syahir bin Md Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study examines Malaysia's border security, its management and threats to Malaysian borders. The study is guided by the conceptual framework consisting of three interrelated concepts: border, security, border security management and securitisation and factors of border insecurity. The study employed qualitative and interpretative method of analysis. Official government documents, views of persons of interests, and academic writings were analysed. The study found that before 2001, generally, Malaysia faced traditional territorial disputes with its neighbours. However, after the September 11, 2001 incident, Malaysia faces non-traditional security threats such as maritime piracy, human trafficking and smuggling and international terrorism. The study also found that the socio-economic conditions of neighbouring states have contributed to the rise of piracy, human trafficking and smuggling and international terrorism in Malaysia's territorial waters. The Malaysian government has enacted legislations, laws and regulations to secure its borders. They include Prevention of Terrorist Act (POTA), Special Offences (Special Measures) Act (SOSMA), the establishment of Eastern Sabah Security Command (ESSCOM), Border Security Agency (AKSEM), and Malaysian Maritime Enforcement Agency (MMEA) as well as government-to-government (G2G) intelligence sharing initiatives. The study among others recommends introduction of biometric screening technology at entry points and more training for its border security personnel.